2012
DOI: 10.1590/s0101-20612012005000029
|View full text |Cite
|
Sign up to set email alerts
|

Sugar fractionation and pectin content during the ripening of guava cv. Pedro Sato

Abstract: Guava is one of the most complete and balanced fruits in in terms of s nutritional value. Highly perishable, due to its intense metabolism during ripening, its shelf life can reach 3 to 5 days under room temperature. The firmness of the green and mature fruits is due mainly to the pectin polymers. The loss of firmness during the guava ripening is due to hydrolytic enzyme activity, which promotes intense solubilization of the cell wall pectins. Given the above, with the purpose of trying to explain the rapid fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…In similar studies, contents of 5.89, 5.7, and 0.72% of pectin in dry mass were reported for gabiroba, guava and araçá-do-campo, respectively. In addition, 0.258% was reported for gabiroba-do-cerrado, the latter being evaluated in fresh mass content (Santos, Petkowicz, Haminiuk, & Cândido, 2010;Abreu, Santos, Abreu, Corrêa, & Lima, 2012;Morzelle et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In similar studies, contents of 5.89, 5.7, and 0.72% of pectin in dry mass were reported for gabiroba, guava and araçá-do-campo, respectively. In addition, 0.258% was reported for gabiroba-do-cerrado, the latter being evaluated in fresh mass content (Santos, Petkowicz, Haminiuk, & Cândido, 2010;Abreu, Santos, Abreu, Corrêa, & Lima, 2012;Morzelle et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the soluble fraction according to the same methodology, 10.0 mL of distilled water, instead of the EDTA solution, were added to the residue on the filter paper, and after one hour of agitation, the mixture was filtered and the supernatant stored. b) Second method using a tetrasodium EDTA solution This was carried out according to the methodology proposed by Abreu et al (2012b), with modifications: 0.25 g of sample (0.25 g pure guava was macerated in advance, without the addition of solvents, with the aid of a mortar and pestle) was weighed and 10.0 mL of a 2.0 mM EDTA solution, pH 7. 0 added.…”
Section: Pectin Extractionmentioning
confidence: 99%
“…"Pedro Sato", due to its extensive production, nutritional value, acceptance (due to its pleasant taste), attractive colour and a high vitamin C content AMATO NETO, 2009;OLIVEIRA et al, 2012). Guava is one of the main raw materials used by the canning industry in Brazil, allowing for various forms of exploitation, for example, puree, pulp, nectar, juice, jam, ice cream and candy (ABREU et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedro Sato, Abreu et al (2012b) suggested that the amount of pectin in guava should be higher than 2.5% in fresh weight (or 15% dry weight). Given these results, a new step in the extraction of pectin was proposed, in the two modified methods by McCready & McComb (1952), that is, the treatment of the residue after the determination of soluble pectin, with cellulase and pectinase in the fractions supernatant and sediment, obtaining insoluble pectin, and cellulase, hemicellulase and pectinase were used in the other treatment, under the same conditions.…”
Section: Pectin Contentsmentioning
confidence: 99%